Living the global city / globalization as local process. - Eade,John(Editor) (Routledge, 1997)
Politicians and academics alike have made globalization the key reference point for interpreting the 1990s. For many, globalization threatens both community and the nation-state. It appears to represent forces beyond human control. Living the Global City documents globalization's impact on everyday lives by drawing on research rather than rhetoric, which lends the book a very different perspective.